Model Pemberdayaan Perempuan Berbasis Pendidikan Nonformal Melalui Program Bank Sampah Bunda Di Desa Bangun Rejo - Rabiatul Adawiyah; Mustangin Mustangin; Arif Sugianto; Muhammad Ilham Akbar (Jurnal Kajian Ilmiah, 2026)
This study aims to examine the model of women's empowerment based on non-formal education through the Bunda Waste Bank Program in Bangun Rejo Village. The research uses a qualitative approach with a descriptive method. Data collection was carried out through observation, interviews, and document studies. Data analysis uses Miles and Huberman's interactive model which includes data reduction, data presentation, and conclusion drawn, with data validity maintained through source triangulation and triangulation techniques. The results of the study show that the women's empowerment model in this program is studied using five stages, namely preparation, social mapping, planning, implementation, and evaluation. The main characteristic of the model lies in a participatory and contextual approach that allows women to be actively involved in the learning process and program management. This research shows that the Bunda Waste Bank Program can be an example of an adaptive, participatory, and sustainable community empowerment model.